Hypersensitivity Reactions to Nonsteroidal Anti-Inflammatory Drugs: An Update - Luis González-Aveledo; Arnaldo Capriles-Hulett; Fernan Caballero-Fonseca; Mario Sánchez-Borges (MDPI AG, 2010)
After beta lactam antibiotics, hypersensitivity reactions to nonsteroidal antiinflammatory drugs are the second cause of hypersensitivity to drugs. Acute manifestations affect the respiratory tract (aspirin exacerbated respiratory disease), the skin (urticaria and angioedema), or are generalized (anaphylaxis). Correct diagnosis and treatment in order to prevent unnecessary morbidity and the potential risk of death from these severe reactions, and to provide proper medical advice on future drug use frequently requires the participation of allergology specialists familiar with these clinical conditions.